HUBUNGAN C-REACTIVE PROTEIN DENGAN PEMANJANGAN PROTHROMBIN TIME PADA PASIEN SIROSIS HATI YANG MENGALAMI PERDARAHAN SALURAN MAKANAN BAGIAN ATAS - Mariadi, IK; Wibawa, IDN; Purwadi, N; Suryadarma, IGA (journal of internal medicine, 2011)
Bacterial infections are common complications in cirrhosis, and cause the systemic in! ammation process. The natureof the relationship between gastrointestinal bleeding and infection in cirrhosis has not been clari" ed. Infection is associatedwith failure to control variceal bleeding and early variceal rebleeding in these patients. Bacterial infections, and particularlyendotoxemia, have been shown to activate the coagulation system and generally to interfere with hemostasis. We performedcross-sectional analytic study in cirrhosis patients with upper gastrointestinal bleeding to assess whether there are any associationbetween in! ammation process (CRP) with defect in haemostatic system (prolongation in prothrombin time). Forty-nine patientswere evaluated, 37 (75.5%) out of these were male and the rest were female. Ninteen out of this with in! ammation process and30 without in! ammation process. Fourteen out of 19 patients (73.7%) in in! ammation group have prolongation on prothrombintime and 12 out of 30 patients (40%) in non in! ammation group have prolongation on prothrombin time. The difference of thisproportion statistically signi" cant (Chi-square test X2: 5.29; p = 0.021). The CRP also have positive correlation with prolongationin prothrombin time (Spearman correlation R = 0.390; p = 0.006). In conclusion there is signi" cant association between CRP andprothrombin time in cirrhosis patients with upper gastrointestinal bleeding.